SYNTHESIS OF EPOXIDATION SOYBEAN OIL RESIN AND ANALYZE MECHANICAL PROPERTIES OF EPOXY ESTER COATING FILM - Huynh Le Huy Cuong; Nguyen Ngoc Phuong (HUIT Journal of Science, 2023)
Epoxy resin DER 671X75 was modified with fatty acids of soybean oil to improve the toughness of epoxy resin. Fatty acids of soybean oil were separated by saponification with sodium hydroxide solution and acidification with acid sulfuric. Extracted fatty acids and the epoxidized soybean oil resin were characterized by Fourier Transform Infrared Spectrometry (FTIR). The results showed the effects of saponification and acidification conditions on the properties of fatty acids. Epoxy ester resin is synthesized from epoxy resin DER 671X75 and fatty acids of soybean oil with a ratio mass of epoxy resin and fatty acids is 1:2 (wt/wt), reaction temperature of 220 oC, and reaction time with 6 hours for the highest reaction level. Epoxy ester resin was able to form coatings film, and mechanical properties of epoxy polymer coatings film were increased.